Perumusan Strategi Bisnis PT XYZ - Roy Hutahaean; Idqan Fahmi; Ahmad Mukhlis Yusuf (School of Business, Bogor Agricultural University (SB-IPB), 2017)
The purpose of this study is to formulate business strategy of XYZ Company. This study used 4 analysis tool Matrixes i.e. IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation), SWOT (Strength, Weaknesses, Opportunities, and Threat), and QPSM (Quantitative Strategic Planning Matrix). The primary and secondary data were used for this study. The IFE and EFE analysis showed weighted values of 2.52; 3.31 in quadrant II, indicating that this company is still in growth and development phase while, through the SWOT analysis, 5 alternative strategies could be concluded i.e. (1) collaboration with government to provide special fleet as domestic transportation to support national shipping industry; (2) collaboration not only with Head company but also with the other multi-stakeholders; (3) Capacity building regarding development of national shipping industry to XYZ employees; (4) establishment of agreement among multi-stakeholders against corruptions, collusion and nepotism; (5) development of a good working mechanism in accordance with the structural organization to increase working efficiency. Lastly, based on QPSM analysis, the main priority in business strategy of XYZ Co. is the capacity building for all of its employees.Keywords: business strategy, IFE,EFE, SWOT Matrix, QSPMAbstrak: Penelitian ini bertujuan memformulasikan strategi bisnis PT. XYZ melalui pendekatan analisis deskriptif. Alat alat analisis yang digunakan, yaitu matrix IFE (Internal factor Evaluation) dan EFE (External Factor Evaluation), SWOT (Strength, Weaknesses, Opportunities, and Threat) dan QSPM (Quantitative Strategic Planning Matrix). Data yang digunakan adalah data primer dan sekunder. Berdasarkan hasil IFE dan EFE diperoleh nilai tertimbang masing masing sebesar (2,523;3,310) sehingga posisi perusahaan dalam matriks IE berada di kuadran II, yaitu tumbuh dan kembangkan. Berdasarkan hasil analisis SWOT diperoleh lima alternatif strategi (1) bekerja sama dengan pemerintah dalam menyiapkan armada khusus untuk pengangkutan dalam negeri sehingga mendukung industri pelayaran nasional; (2) bekerja sama dengan pihak lain diluar Perusahaan induk; (3) peningkatan kapasitas tentang pengembangan industri pelayaran nasional kepada staff; (4) membangun kesepakatan dengan pihak-pihak terkait untuk memberantas korupsi, kolusi dan nepotisme (5) membangun mekanisme kerja yang baik sesuai dengan struktur organisasi sehingga dapat meningkatkan efisiensi kerja. Berdasarkan analisis QSPM prioritas utama dalam perumusan strategi bisnis PT.XYZ adalah peningkatan kapasitas seluruh staff.Kata kunci: perumusan strategi, IFE, EFE, SWOT Matrix, QSPM